Differences in emotions and cognitions experienced in contamination aversion. Issue 3 (22nd August 2018) - Rouel, Melissa; Stevenson, Richard J.; Milne-Home, Josephine; Smith, Evelyn
A current model of contamination aversion suggests that it has distinct affective and cognitive components that interact to respond to threats. The affective component involves disgust and responds preferentially to direct contaminants (e.g., feces). The cognitive component involves obsessive beliefs and responds preferentially to indirect contaminants (e.g., money). This study examined characteristics of the two components by comparing emotional and cognitive responses to different contaminants. In total, 47 participants completed behavioral avoidance tasks with direct, indirect, and harmful contaminants. Participants rated their disgust, fear of contamination, and threat estimation while in contact with each contaminant. The contaminants produced different emotional and cognitive responses, suggesting the differential involvement of affective and cognitive factors depending on the type of threat. Additionally, it was found that disgust did not habituate over time in contact with contaminants, whereas fear of contamination and threat estimation appeared to decline. Clinical and theoretical implications are discussed.